The barriers of implementing green residential building development in Kedah / Adila Anor and Mohamad Haszirul Mohd Hashim - Anor, Adila; Mohd Hashim, Mohamad Haszirul (2023)
The barriers to green residential building development in Kedah may include high cost, lack of market demand, limited supply, and lack of incentives. This research aimed to determine the barriers to green residential development in Kedah. This research was conducted using a questionnaire as the main research instrument and a case study of a green residential area in Kedah. This questionnaire was distributed via a Google Form link, out of which 58 were returned and used for analysis. The respondents consisted of 34.5% engineers, 27.6% project managers, followed by 20.7% developers, and 8.6% contractors and consultants. The findings of this research aimed to enhance knowledge, facilitate financial assistance, enforce regulations, encourage cooperation, and increase resource availability, ultimately making it easier to implement sustainable practices and overcome barriers to green residential construction in Kedah.